Hydrocarbon accumulation model for Neogene traps in the Chengdao area, Bohai Bay Basin, China. (November 2016) - Liu, Hua; Zhao, Donggao; Jiang, Youlu; Zhuang, Mei; Liu, Ying
Abstract: Chengdao is an offshore area in the Bohai Bay Basin that contains approximately 25.7 × 10 8  bbl of oil and gas reserves within the sandstone reservoirs in Neogene strata. However, previous predictions of hydrocarbon accumulation in Neogene traps are inaccurate, resulting in a current failure rate of 50% when drilling for hydrocarbons in this area. To build an improved exploration model for Neogene traps, we select 92 traps from Neogene strata in the Chengdao area to quantify the filling degree, which is an indicator of hydrocarbon accumulation efficiency. The quantified filling degree is based on actual geological and exploration data and differs significantly among various trap types. The filling degree of traps also varies significantly with their structural locations and decreases generally from the northwest to the southeast along the Chengbei Fault zone. Vertically, the filling degree is highly heterogeneous, initially increasing from the bottom to the middle of Neogene strata and then decreasing towards the top of the strata. These Neogene hydrocarbon reservoirs are sourced from the Paleogene, and as they lay vertically away from the source rocks, their hydrocarbon enrichment is constrained largely by hydrocarbon migration distance and vertical migration pathways. The sealing capacity of faults and cap rocks, sandbody orientation and reservoir sedimentary facies determine the maximum column height, which in turn affects the amount of hydrocarbon accumulation within these traps. A scatter plot analysis of individual controls and volumetric filling for each trap type is compiled using multivariate linear regression analysis to quantify controls and the dominant control of hydrocarbon accumulation is determined. Highlights: Volumetric filling degree is an excellent indicator of hydrocarbon accumulation for complex or irregular sandbodies. Neogene hydrocarbon reservoirs are far vertical away from source rocks in Chengdao area, constrained by source rocks, migration distances and vertical pathway. Sealing capacity of faults and cap-rocks determines the largest accumulation amount of hydrocarbons. The scatter plot analysis between individual controls and volumetric filling can identify the dominant controls on hydrocarbon accumulation. Multivariate linear regression analysis was used to quantity the controls on trap filling degree.